2013
DOI: 10.1177/0009922813501377
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Residents’ Perceptions of Family-Centered Rounds as Part of Postgraduate Training

Abstract: Concerns regarding discomfort, attending approach and efficiency are potential barriers to residents' full acceptance of FCRs that should be addressed to improve the efficacy of postgraduate pediatric training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…The initial concerns voiced by our CTICU staff, as well as in published reports, regarding privacy issues, increasing parental anxiety, increasing duration of rounds, decreasing teaching during rounds, and concerns for parents' understanding of complex discussions [8][9][10][11] were not found to be true in our experience. Our findings are more consistent with those of Kuo et al, 13 who reported that family participation during rounds was associated with higher parental satisfaction, improved and consistent transfer of medical information, discussion of care plan, and participation in decision making; and Phipps et al, 10 who reported that parental presence during rounds did not inhibit teaching.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The initial concerns voiced by our CTICU staff, as well as in published reports, regarding privacy issues, increasing parental anxiety, increasing duration of rounds, decreasing teaching during rounds, and concerns for parents' understanding of complex discussions [8][9][10][11] were not found to be true in our experience. Our findings are more consistent with those of Kuo et al, 13 who reported that family participation during rounds was associated with higher parental satisfaction, improved and consistent transfer of medical information, discussion of care plan, and participation in decision making; and Phipps et al, 10 who reported that parental presence during rounds did not inhibit teaching.…”
Section: Discussionmentioning
confidence: 89%
“…Some concerns voiced by staff regarding inclusion of parents during rounds include privacy issues, increasing parents' anxiety, increasing duration of rounds, decreasing teaching during rounds, and concerns for parents' understanding of complex discussions. [8][9][10][11] Phipps et al, 10 in an observational study, showed that parental presence during rounds did not inhibit teaching during rounds, although admittedly the data on this topic are controversial. Cameron et al, 12 in a prospective, observational, and survey-based study, showed that 40% of attending physicians limited their teaching during rounds to avoid exposing the knowledge gaps among house staff.…”
mentioning
confidence: 99%
“…1 Literature on trainee perception of FCR universally cites fear of appearing less knowledgeable in front of patients and families as a barrier to didactic teaching on rounds. 2,3 This fear may lead trainees to forgo asking questions or offering answers to those posed by attending physicians, which results in suboptimal discussion about patient management. 2,3 In addition, fear of sharing sensitive patient information on FCR also serves as a barrier because trainees attempt to balance the emotional needs of patients and families with the need for frank clinical discussion.…”
mentioning
confidence: 99%
“…2,3 This fear may lead trainees to forgo asking questions or offering answers to those posed by attending physicians, which results in suboptimal discussion about patient management. 2,3 In addition, fear of sharing sensitive patient information on FCR also serves as a barrier because trainees attempt to balance the emotional needs of patients and families with the need for frank clinical discussion. 2,4 Anecdotally, this is particularly true when it comes to discussion of appropriate differential diagnoses, especially when a difficult diagnosis such as malignancy is possible.…”
mentioning
confidence: 99%
See 1 more Smart Citation